2017
DOI: 10.1002/clc.22651
|View full text |Cite
|
Sign up to set email alerts
|

Fragmented QRS complex predicts contrast‐induced nephropathy and in‐hospital mortality after primary percutaneous coronary intervention in patients with ST‐segment elevation myocardial infarction

Abstract: Background Contrast‐induced nephropathy (CIN) is associated with increased mortality after primary percutaneous coronary intervention (PCI) for ST‐segment elevation myocardial infarction (STEMI). Recently, fragmented QRS complex (fQRS) on 12‐lead electrocardiography has been introduced as a marker of cardiovascular disease and is associated with increased morbidity and mortality. Hypothesis fQRS on ECG is associated with CIN and in‐hospital mortality after primary PCI in patients with STEMI. Methods Eight hun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 28 publications
(71 reference statements)
0
49
0
Order By: Relevance
“…There was no subgroup difference between prospective and retrospective studies ( I 2 = 0%). Subgroup analysis of three studies (Kurtul & Duran, ; Tanriverdi et al., ; Yildirim et al., ) with shorter follow‐up time (in‐hospital or short‐term mortality) still shows significant association (RR 5.58; 95% CI 2.65–11.75) with low heterogeneity ( I 2 = 0%). Funnel plot did not suggest publication bias (Figure ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…There was no subgroup difference between prospective and retrospective studies ( I 2 = 0%). Subgroup analysis of three studies (Kurtul & Duran, ; Tanriverdi et al., ; Yildirim et al., ) with shorter follow‐up time (in‐hospital or short‐term mortality) still shows significant association (RR 5.58; 95% CI 2.65–11.75) with low heterogeneity ( I 2 = 0%). Funnel plot did not suggest publication bias (Figure ).…”
Section: Resultsmentioning
confidence: 97%
“…Four studies were excluded because they did not report outcome of interest. Therefore, three retrospective and two prospective cohort studies with 888 fQRS and 1,628 non‐fQRS STEMI patients were included in this meta‐analysis (Akgul et al., ; Kurtul & Duran, ; Tanriverdi, Dursun, Colluoglu, & Kaya, ; Uslu et al., ; Yildirim et al., ). The clinical characteristics are described in Table .…”
Section: Resultsmentioning
confidence: 99%
“…However, it has been suggested that several inflammatory markers—including white blood cell count, neutrophil count, C‐reactive protein, big endothelin‐1, and urine neutrophil gelatinase‐associated lipocalin—are also important predictors of CI‐AKI . In addition, fragmented QRS complex on 12‐lead electrocardiography has also been shown to be an independent predictor of postprocedural CIN in patients undergoing primary percutaneous coronary intervention …”
Section: Discussionmentioning
confidence: 99%
“…16,17 In addition, fragmented QRS complex on 12-lead electrocardiography has also been shown to be an independent predictor of postprocedural CIN in patients undergoing primary percutaneous coronary intervention. 18 Several therapies have been investigated for CIN prevention, Recently, a novel strategy to achieve a high urine output through forced diuresis while maintaining euvolemia has been developed using the RenalGuard system. 20 A possible mechanism by which high urine output through forced diuresis decreases the risk of CIN is by limiting the contrast-nephron exposure time through acceleration of tubule and collecting duct flow, reducing sledging and precipitation of contrast material, clearing the contrast from the kidney before significant damage occurs.…”
Section: Discussionmentioning
confidence: 99%
“…
We read with great interest the article written by Kurtul and Duran, which was recently published in Clinical Cardiology, demonstrating the role of the fragmented QRS complex (fQRS) as a new predictor of contrast-induced nephropathy and in-hospital mortality after primary percutaneous coronary intervention (PCI) in patients with ST-segment elevation myocardial infarction (STEMI). 1 The authors found that in STEMI patients, fQRS in more than 3 leads on surface electrogram is a strong independent predictor of inhospital mortality, with an odds ratio of 9.062 (95% confidence interval [CI]: 1.722-47.681, P = 0.009) on multivariate analysis. At the same time, fQRS demonstrated to represent an independent predictor of contrast-induced nephropathy (CIN) in patients undergoing PCI for STEMI, with an odds ratio for CIN of 3.125 (95% CI: 1.127-8.695, P = 0.029).
…”
mentioning
confidence: 99%